Morphometric traits as drivers for module structures and species specialization: a study about the hermit crab–gastropod networks from three different regions on the Brazilian coast. (12th October 2021) - da Silva, A. R.; Rodrigues, G. F. B.; Borthagaray, A. I.; Costa, R. C.; Castilho, A. L.
Abstract: The relationship between hermit crabs (Paguroidea) and gastropod shells has attracted the attention of researchers toward a network approach. These networks seem to present recurrent patterns that are often modular, i.e., a pattern in which the network can be divided into compartments that represent species interacting more with species belonging to its own compartment than with species composing another compartment. A modular interaction network occurs when species tend to interact more intensively within subsets of species (modules) than with species outside of it. Since modularity is a characteristic in which different hermit crabs interact with different sub‐sets of shells, we proposed that these patterns should be a reflection of different morphometric traits, as well as that species specialization (measure which indicates if a given species is specialist or generalist in resource use) could be related to such traits. Three different hermit crab–shell networks in which the modularity and species specialization have already been determined were chosen. The animals were sampled in three different regions with the same sampling effort in the same type of substrate. After sampling, the animals were taken to the laboratory where they were identified and measured. A PERMANOVA was used for the hermit crab morphometric traits from each region using each compartment as grouping variable. In order to test if morphometric traits influence species specialization (d′), linear mixed models were created and selected through Akaike's Information Criterion. Our data show that hermit crabs presented different morphometric traits in each module they occupied. Also, d′ was influenced by morphometric traits; thus, hermit crabs with different sizes need different types of shells, which reflect in different specialization levels. Abstract : The relationship between hermit crabs and gastropod shells has attracted the attention of researchers toward a network approach. These networks seem to present recurrent patterns that are often modular, that is, a pattern which the network can be divided in compartments. A modular interaction network occurs when species tend to interact more intensively within subsets of species (modules) than with species outside of it. Three different hermit crab‐shell networks in which the modularity and species specialization have already been determined were chosen for the study. The animals were sampled in three different regions with the same sampling effort in the same type of substrate. Our data show that hermit crabs presented different morphometric traits in each module they occupied.